2016
DOI: 10.1007/s12600-016-0513-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a Hog1-type MAPK, MlpHog1, from Melampsora larici-populina

Abstract: The obligate biotrophic fungus Melampsora larici-populina (Mlp) causes devastating poplar foliar rust disease. In pathogens, the Hog1-type mitogen-activated protein kinase (MAPK) gene is involved in both pathogenesis and the response to various stresses, including osmotic stress. However, there are few reports on its role in M. larici-populina. In the present study, we identified and characterized the Hog1-type MAPK gene, MlpHog1, in M. larici-populina. The MlpHog1 protein consists of 356 amino acids and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In our previous study, partial complementation of the hyperosmotic stress response defect of the F. graminearum Hog1 mutant by the MlpHog1 gene demonstrated the functional conservation MlpHog1 and FgHog1 (Yu et al, 2016). Unfortunately, at present, this poplar rust fungus still cannot be genetically manipulated to understand the function of genes of interest in M. laricipopulina, even in a host-induced RNAi system (Qi et al, 2018).…”
Section: Discussionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, partial complementation of the hyperosmotic stress response defect of the F. graminearum Hog1 mutant by the MlpHog1 gene demonstrated the functional conservation MlpHog1 and FgHog1 (Yu et al, 2016). Unfortunately, at present, this poplar rust fungus still cannot be genetically manipulated to understand the function of genes of interest in M. laricipopulina, even in a host-induced RNAi system (Qi et al, 2018).…”
Section: Discussionsmentioning
confidence: 99%
“…The vector pFL2:: MlpHog1 (Yu et al, 2016) was transformed into protoplasts of the M. oryzae Hog1 mutant Δ OSM1 as described previously (Sweigard et al, 1992). Geneticin‐resistant transformants were confirmed by PCR analysis with primers MlpHog1‐F/RP27 and pFL2 insert/R (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, few pathogenicity genes have been identified and characterized in other fungi like M. grisea Hog1 homolog OSM1 which is essential for survival because it is required for tolerating desiccation, UV-light, and osmotic stresses (Dixon et al 1999). MlpHog1 gene may play a role in the infectious growth of Melampsora larici-populina and the response of the fungus to various environmental stresses (Yu et al 2016).…”
Section: Cereal Research Communications 46 2018mentioning
confidence: 99%
“…In a study on necrotrophic fungus which causes the southern corn leaf blight, Cochliobolus heterostrophus Hog1 MAPK mutants produced smaller appressoria and caused weaken disease symptoms on maize (Igbaria et al, 2008). In a recent study, mutant complementation of Melamspora larici-populina Hog1 MAPK (MlpHog1) suggested that the protein could be involved in various environmental stresses and infectious growth (Yu et al, 2016). However, the absence of Hog1 MAPK did not perpetually affect the fungal pathogenicity as shown in the studies on Colletotrichum orbiculare (Kojima et al, 2004) and Bipolaris oryzae (Moriwaki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%